Second primary malignancies in multiple myeloma: an overview and IMWG consensus - Musto, Pellegrino; Hillengaß, Jens (Annals of oncology, 2017)
Background. Therapeutic advancements following the introduction of autologous stem cell transplantation and ‘novel’ agents have significantly improved clinical